(NpUNKTUACIQ FRANCUZSKOGO QZYKA (B:s (Nu^EBNOE POSOBIE (B/s - (NwEDENINA(B, (Nl@DMILA gEORGIEWNAs ((NmOSKWA (B:s (NwYS[AQ [KOLA (B,s, 1975)
(NsPISOK LIT(B.: (NS(B. 162-165s
Keywords: (NfRANCUZSKIJ QZYK (B- (NpUNKTUACIQs